The Effectiveness of a Training Program Based on Social Skills in Raising Awareness among Mothers to Reduce the Symptoms of Sexual Problems among Their Girls with Autism Spectrum Disorder After Puberty - Anza, Abrar Youssef Abu; Al-Sharaa, Faisal Khalif; Khamis, Esra’ Mohammad Mustfa; Al-Moumani, Islam Shukri Abdul Aziz (Journal of Ecohumanism, 2024)
The current study aimed to identify the effectiveness of a training program in educating mothers to reduce the symptoms of sexual problems in their adolescent girls with autism spectrum disorder after puberty among a sample of mothers of adolescent girls with autism spectrum disorder in Zarqa Governorate, the sample consisted of (30) mothers of adolescent girls with autism spectrum disorder who suffer from sexual problems. The mothers were randomly distributed into two experimental groups (n=15) mothers. For those who participated in the training program designed for the current study and the control group, which consisted of (n=15) mothers, as it was not exposed to any training intervention, for this study, the following tools were prepared: The Sexual Aspects Scale as a pre-and post-test procedure. A training program was also designed to educate mothers about sexual problems among their adolescent girls with autism spectrum disorder after puberty, which took two months to implement. The results of the study indicated that there were statistically significant differences (α = 0.05) in the effectiveness of the training program in reducing the level of sexual problems suffered by adolescent girls with autism spectrum disorder among the mothers of the experimental group that underwent the training program. The study concluded that there were statistically significant differences at the significance level (α = 0.05) in the scores of mothers of adolescent girls with autism spectrum disorder on the sexual aspects scale according to the group (experimental, control). The differences were in favor of the experimental group who were exposed to the training program compared to members of the control group; the results also found that the size of the impact of the treatment program was significant in the dependent variable, which is a measure of sexual aspects.